Impact of diet and nutraceutical supplementation on inflammation in elderly people. Results from the RISTOMED study, an open-label randomized control trial. Issue 4 (August 2016) - Ostan, R.; Béné, M.C.; Spazzafumo, L.; Pinto, A.; Donini, L.M.; Pryen, F.; Charrouf, Z.; Valentini, L.; Lochs, H.; Bourdel-Marchasson, I.; Blanc-Bisson, C.; Buccolini, F.; et al.
Summary: Background & aims: Eating habits may influence the life span and the quality of ageing process by modulating inflammation. The RISTOMED project was developed to provide a personalized and balanced diet, enriched with or without nutraceutical compounds, to decrease and prevent inflammageing, oxidative stress and gut microbiota alteration in healthy elderly people. This paper focused on the effect on inflammation and metabolism markers after 56 days of RISTOMED diet alone or supplementation with three nutraceutical compounds. Methods: A cohort of 125 healthy elderly subjects was recruited and randomized into 4 arms (Arm A, RISTOMED diet; Arm B, RISTOMED diet plus VSL#3 probiotic blend; Arm C, RISTOMED diet plus AISA d -Limonene; Arm D, RISTOMED diet plus Argan oil). Inflammatory and metabolism parameters as well as the ratio between Clostridium cluster IV and Bifidobacteria (CL/B) were collected before and after 56 days of dietary intervention, and their evolution compared among the arms. Moreover, participants were subdivided according to their baseline inflammatory parameters (erythrocytes sedimentation rate (ESR), C-Reactive Protein, fibrinogen, Tumor Necrosis Factor-alfa (TNF-α), and Interleukin 6) in two clusters with low or medium–high level of inflammation. The evolution of the measured parameters was then examined separately in each cluster. Results: Overall, RISTOMED diet alone or with each nutraceutical supplementation significantly decreased ESR. RISTOMED diet supplemented with d-Limonene resulted in a decrease in fibrinogen, glucose, insulin levels and HOMA-IR. The most beneficial effects were observed in subjects with a medium–high inflammatory status who received RISTOMED diet with AISA d -Limonene supplementation. Moreover, RISTOMED diet associated with VSL#3 probiotic blend induced a decrease in the CL/B ratio. Conclusions: Overall, this study emphasizes the beneficial anti-inflammageing effect of RISTOMED diet supplemented with nutraceuticals to control the inflammatory status of elderly individuals.